A deterministic quantum dot micropillar single photon source with >65% extraction efficiency based on fluorescence imaging method. Issue 1 (December 2017) - Liu, Shunfa; Wei, Yuming; Su, Rongling; Su, Rongbin; Ma, Ben; Chen, Zesheng; Ni, Haiqiao; Niu, Zhichuan; Yu, Ying; Wei, Yujia; Wang, Xuehua; Yu, Siyuan
Abstract We report optical positioning of single quantum dots (QDs) in planar distributed Bragg reflector (DBR) cavity with an average position uncertainty of ≈20 nm using an optimized photoluminescence imaging method. We create single-photon sources based on these QDs in determined micropillar cavities. The brightness of the QD fluorescence is greatly enhanced on resonance with the fundamental mode of the cavity, leading to an high extraction efficiency of 68% ± 6% into a lens with numerical aperture of 0.65, and simultaneously exhibiting low multi-photon probability (g(2) (0) = 0.144 ± 0.012) at this collection efficiency.